1998
DOI: 10.1016/s0022-2275(20)32468-8
|View full text |Cite
|
Sign up to set email alerts
|

Lipoprotein lipase is expressed in cultured Schwann cells and functions in lipid synthesis and utilization

Abstract: We have previously demonstrated that lipoprotein lipase (LPL; triacylglycero-protein acylhydrolase, EC 3.1.1.34) is most likely expressed in the non-neuronal cells of the spinal cord, and glial cells may thus be the site of expression in the peripheral nervous system as well. We investigated the expression of LPL in cultured 1.17 cells, an immortalized rat sciatic nerve Schwann cell line. The 1.17 cells were shown to express LPL mRNA by reverse transcriptase-polymerase chain reaction analysis. The 1.17 Schwann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(6 citation statements)
references
References 48 publications
(45 reference statements)
1
5
0
Order By: Relevance
“…In our study, LPL immunoreactivity was widely present throughout all major regions of human brain tissue, with moderate to high immunoreactivity in subgroups of neurons, extensive immunoreactivity in microglia, and sporadic immunoreactivity in astrocytes and oligodendroglia. LPL immunostaining in Schwann cells associated with cranial nerves is in agreement with previously published in vitro data (Huey et al 1998 andFerreira et al 2002), and the presence of LPL in the brain microvasculature supports findings in the rat brain (Shirai et al 1986).…”
Section: Discussionsupporting
confidence: 91%
“…In our study, LPL immunoreactivity was widely present throughout all major regions of human brain tissue, with moderate to high immunoreactivity in subgroups of neurons, extensive immunoreactivity in microglia, and sporadic immunoreactivity in astrocytes and oligodendroglia. LPL immunostaining in Schwann cells associated with cranial nerves is in agreement with previously published in vitro data (Huey et al 1998 andFerreira et al 2002), and the presence of LPL in the brain microvasculature supports findings in the rat brain (Shirai et al 1986).…”
Section: Discussionsupporting
confidence: 91%
“…We have previously shown that LPL mRNA and cell-surface activity are expressed by cultured Schwann cells isolated from rat peripheral nerve. Inhibiting LPL activity with a polyclonal anti-LPL antiserum inhibited the cells' ability to utilize exogenous triacylglycerol-derived FFA for incorporation into newly synthesized phospholipids, triacylglycerol, and cholesteryl esters (6). Based on these results, we hypothesized that LPL in the nerve functions in maintenance of nerve myelin and may be involved in the recycling of myelin lipids that occurs upon nerve injury.…”
Section: Discussionmentioning
confidence: 96%
“…Approximately equalsized portions of the contralateral uninjured ner ves were treated likewise. Duplicate aliquots of the supernatants were assayed for LPL activity as described (6), and data are expressed as nEq of FFA released per min per g nerve tissue.…”
Section: Lpl Activity In Proximal and Distal Segments Of Crush-injured Nervementioning
confidence: 99%
See 2 more Smart Citations